(3GdTaG HJYQja Mbhb GdeUWais - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGSeg GdCSei CeG HYO CTQb Gddg bdHi hbdHc HGfhGQ Gdjbjf s
(3BNQgG (B:s
(3hgh CMb HGSe GdaSb ef GSe Gdabg ajJbOe Edjg ai Pdc heDNQ hdG JbHd aJhGg hdG TgGOJg hgj LQMg KGHJg ajg hjfaV ai Gddg bGd GdbGVi gf GfJgi Gdbhd hgh MSHfG hfYe Gdhcjd s
(3HChdgG bQGAGJs
(3fSNI NRGFfjI eLOhdI HGdPgHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
Keywords: (3GdJGQjNs